From Protein Communication to Drug Discovery - Persico, Marco; Di Dato, Antonio; Orteca, Nausicaa; Fattorusso, Caterina; Novellino, Ettore; Andreoli, Mirko; Ferlini, Cristiano (Current Topics in Medicinal Chemistry, 2015)
The majority of functionally important biological processes are regulated by allosteric communication within individual proteins and across protein complexes. The proteins controlling these communication networks respond to changes in the cellular environment by switching between different conformational states. Targeting the interface residues mediating these processes through the rational identification of molecules modulating or mimicking their effects holds great therapeutic potential. Protein-protein interactions (PPIs) have shown to have a high degree of plasticity since they occur through small regions, called hot spots, which are included in binding surfaces or in binding clefts of the proteins and are characterized by a high degree of complementarity. This prompted several researchers to compare the protein structure to human grammar proposing terms like “protein language”. The decoding of this language represent a new paradigm not only to clarify the dynamics of many biological processes but also to improve the opportunities in drug discovery. In this review, we try to give an overview on intra-molecular and inter-molecular protein communication mechanisms describing the protein interaction domains (PIDs) and short linear motifs (SLiMs), which delineate the authentic syntactic and semantic units in a protein. Moreover, we illustrate some novel approaches performed on natural compounds and on synthetic derivatives aimed at developing new classes of potential drugs able to interfere with intra-molecular and inter-molecular protein communication.
Keywords: Hot spots